HEALTH EDUCATION AND PESTICIDE MANAGEMENT: EXTENSION ACTION WITH RURAL WORKERS: HEALTH EDUCATION AND PESTICIDE MANAGEMENT: EXTENSION ACTION WITH RURAL WORKERS - Santos, Lucas Emanuel dos; Santana, Maria Flávia Oliveira de; Bernardino, Victória Fortaleza; Sousa, Irys Natalhia Maia de; Silva, Meirielly Kellya Holanda da (REVISTA ELETRÔNICA EXTENSÃO EM DEBATE, 2025)
This article presents the actions of an extension project aimed at promoting the health of rural workers in Arapiraca/AL, with a focus on mitigating the impacts of the use of pesticides. Through an intersectoral discussion group, made up of professionals from different areas and rural workers, problems such as the indiscriminate use of pesticides and difficulty in accessing Personal Protective Equipment (PPE) were identified. As interventions, improvements in inspection, training and awareness campaigns were proposed. Educational materials were also created, including informative booklets on first aid and pesticide poisoning, in addition to training for Rural Workers and Community Health Agents. The project highlighted the role of the university in developing solutions to community problems, promoting health and safety of rural workers and reinforcing the triad of teaching, research and extension.